Eating disorder symptoms and perfectionism in female athletes - Donti, O.; Panidi, I.; Gaspari, V.; Donti, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Eating disorders are complex psychiatric disorders impairing everyday life, health, and development (1). For athletes of aesthetic sports, in addition to physical and psychosocial health, eating disorders may also be detrimental for sports performance (2). Among personality traits implicated in the etiology of eating disorders, perfectionism is a central variable in adults (3). However, evidence is lacking in adolescent athletes. Thus, the aim of this study was to examine eating disorder symptoms and perfectionism in adolescent rhythmic gymnasts. METHODS: Sixty-two female rhythmic gymnasts (34 international and 28 recreational level gymnasts), aged 13-15 years, completed the Eating Attitudes Test 26 (EAT-26), the Sport Perfectionism Questionnaire (SPQ), the Social Desirability Scale (SDS) and a questionnaire which included age, weight, height information as well as training and competition details. RESULTS: Twenty of the 62 athletes (32.26%) scored *20 in EAT-26. International level gymnasts scored higher than recreational in EAT-26 (p = 0.002) and the Dieting subscale (p = 0.034), with no differences between groups in the Perfectionistic Strivings (p = 0.610) and Perfectionistic Concerns factors (p = 0.680). Multiple regression analysis of all gymnasts showed that Perfectionistic Strivings and Negative Reactions to Imperfection, accounted for 22.5% of the variance in EAT-26 (adjusted R2 = 0.225, F = 18.219, p * 0.001). CONCLUSION: International level adolescent rhythmic gymnasts exhibit higher prevalence of eating pathology than recreational level gymnasts, suggesting that participation in sports where leanness is associated with performance is an important risk factor for developing eating disorders, and especially in adolescent athletes. Although striving for perfection is generally considered an adaptive dimension of perfectionism, the present study shows that Perfectionistic Strivings and Negative Reactions to Imperfection seem relevant for gymnasts dieting behavior.